IMPLEMENTATION OF TEXT TRANSFORMATION IN PHYSICS EDUCATION TO REDUCE STUDENTS’ MISCONCEPTION - Soeharto Soeharto (JETL (Journal of Education, Teaching and Learning), 2016)
This research aimed to know the effect of  text transformation in educational physics especially Impuls and momentum to reduce students’ misconception. This study was held at state senior high school (SMAN) 2 in Pontianak, West Borneo.  The instrument in this study has made with diagnostic test using  certainly of responden index method. The research design in this study using one group pretest-posttest design. Population in this research is all students of science major in state senior high school 2 in Pontianak. This study have found that implementation of text transformation giving effect significantly to reduce students’ misconception according Wilcoxon test (Z = -3,418, p = 0.01). However, this research is not finding corelation which is significantly between skill to make a note using text transformation and reduction of students’ misconception ( = 0.119, p = 0.490). The value of effect size in this research is 1.65.